2013
DOI: 10.1094/pdis-11-12-1010-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Lily Blight and Wilt Caused by Fusarium tricinctum in China

Abstract: Lily (Lilium spp.) is one of the most well-known horticultural crops, and plays an important economic role in China. In September 2011, wilted plants were observed on Lilium oriental hybrid cultivar ‘Sorbonne’ growing in Longde County, Ningxia Hui Autonomous Region, China. Disease symptoms included wilting, stem and root rot, brown spots of bulbs and then bulbs rotting and spalling from the basal disc, plus a progressive yellowing and defoliation of the leaves from the base. Diseased plants were sampled from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, F. tricinctum was found as endophytic species in healthy trees and healthy seedlings of Persian oak trees in Iran ( Alidadi et al, 2019 ; Supplementary Table 1 ). Our work proved that F. tricinctum was the pathogen causing bulbs rotting and spalling from the basal disc, as well as progressive yellowing and defoliation of the leaves in lilies and Lanzhou lilies ( Li et al, 2013 ; Shang et al, 2014 ). Interestingly, we also found that F. tricinctum was involved in root rot of Chinese herbal medicine, e.g., Angelica sinensis and wolfberry ( Liu et al, 2021 ; Uwaremwe et al, 2022 ).…”
Section: The Distribution and Ecology Of Fusarium Tricinctummentioning
confidence: 51%
“…In addition, F. tricinctum was found as endophytic species in healthy trees and healthy seedlings of Persian oak trees in Iran ( Alidadi et al, 2019 ; Supplementary Table 1 ). Our work proved that F. tricinctum was the pathogen causing bulbs rotting and spalling from the basal disc, as well as progressive yellowing and defoliation of the leaves in lilies and Lanzhou lilies ( Li et al, 2013 ; Shang et al, 2014 ). Interestingly, we also found that F. tricinctum was involved in root rot of Chinese herbal medicine, e.g., Angelica sinensis and wolfberry ( Liu et al, 2021 ; Uwaremwe et al, 2022 ).…”
Section: The Distribution and Ecology Of Fusarium Tricinctummentioning
confidence: 51%
“…The affected tissue continues to decay until the entire bulb undergoes dry rotting (Bian, 2016 ; Jiao et al, 2021 ). BRD and wilt in the Lilium oriental hybrid cultivar “Sorbonne” are caused by Fusarium tricinctum (Corda) Sacc., Fusarium oxysporum , and Fusarium solani (Li et al, 2013 ; Cao et al, 2018 ). In addition, F. tricinctum and Aspergillus flavus not only cause wilt disease in Chinese ornamental lilies but also affect edible lilies in Lanzhou (Shang et al, 2014 ; Gong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%